Nutrition in City Ecosystems (NICE): Protocol of a multi-sectoral development project to improve food and nutrition security of secondary city populations in Bangladesh, Kenya and Rwanda - Speich, Cornelia; Barth-Jaeggi, Tanja; Musard, Capucine; Havugimana, Cassien; Nwokoro, Charles; Gakuba, Elvis; Zamil, Farhad; Sécula, Florence; Thönnissen, Carmen; Six, Johan; Kraemer, Klaus; van Zutphen, Kesso Gabrielle; et al. (Frontiers in Public Health, 2023)
Background: Secondary cities tend to be better linked with local food systems than primate cities, acting as important platforms to trade agricultural produce with rural surrounding. COVID-19, conflicts and climate change continue to expose inefficiencies in food systems and have further exacerbated malnutrition, calling for substantial food systems transformations. However, tackling current food systems’ challenges requires new approaches to ensure food and nutrition security. Nutritious and agroecologically produced food offer the potential to transform food systems by improving diets and alleviating pressure on the environment, as well as by creating jobs and reducing poverty. This paper describes the design of a project by a Swiss public-private consortium to improve food and nutrition security and to reduce poverty in city ecosystems in six secondary cities in Bangladesh, Kenya and Rwanda through governance/policy and supply and demand side interventions. Methods: The Nutrition in City Ecosystems (NICE) project promotes well-balanced nutrition for city populations through interdisciplinary agricultural, food, and health sector collaborations along city-specific value chains. Adopting a transdiciplinary systems approach, the main interventions of NICE are (i) advocacy and policy dialogue, (ii) building of decentralized institutional capacity in multi-sectoral collaborations, (iii) support of data-driven planning, coordination and resource mobilization, (iv) anchoring of innovations and new approaches in city-level partnerships, (v) capacity building in the agricultural, retail, health and education sectors, as well as (vi) evidence generation from putting policies into practice at the local level. NICE is coordinated by in-country partners and local offices of the Swiss public-private consortium partners. Discussion: The NICE project seeks to contribute to urban food system resilience and enhanced sustainable nutrition for city populations by (A) strengthening urban governance structures involving key stakeholders including women and youth, (B) generating income for producers along the supply chain, (C) triggering change in producers’ and consumers’ behaviour such that nutritious and agroecologically produced foods are both in demand as well as available and affordable in urban markets, and (D) allowing a scale up of successful approaches to other national and international cities and city networks.